2023
DOI: 10.1155/2023/8469372
|View full text |Cite
|
Sign up to set email alerts
|

Confirmed Malaria Cases in Children under Five Years: The Influence of Suspected Cases, Tested Cases, and Climatic Conditions

Kassim Tawiah,
Killian Asampana Asosega,
Richard Kwame Ansah
et al.

Abstract: Tropical and potentially fatal malaria is brought on by the parasite Plasmodium spp which spreads through infected female anopheles mosquitoes within the human populations. In Ghana, malaria is endemic and perennial, with distinct seasonal fluctuations in the northern part. Children aged below five years are among the population most vulnerable to malaria in Ghana. This study’s goal is to establish how suspected malaria cases, tested malaria cases, and climatic conditions impact confirmed malaria cases in chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Reference 3 revealed that Malaria infection remains one of the main killers of children aged 6–59 months. Reference 4 showed that the number of confirmed malaria cases in children under 5 years increases with increase in rainfall and the number of tested cases reduces with increase in temperature. India contributes to 1.7% of the global malaria cases, with a significant proportion of fatalities occurring in children under the age of five within the country.…”
Section: Introductionmentioning
confidence: 99%
“…Reference 3 revealed that Malaria infection remains one of the main killers of children aged 6–59 months. Reference 4 showed that the number of confirmed malaria cases in children under 5 years increases with increase in rainfall and the number of tested cases reduces with increase in temperature. India contributes to 1.7% of the global malaria cases, with a significant proportion of fatalities occurring in children under the age of five within the country.…”
Section: Introductionmentioning
confidence: 99%